To mitigate or to adapt? Collective action under asymmetries in vulnerability to losses - Esther Blanco; E. Glenn Dutcher; Tobias Haller (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
Many policies addressing global climate change revolve around the implementation of mitigation and adaptation strategies. We experimentally examine subjects? choices in a climate change game where subjects are put into groups where they face a potential damage and have the choice to invest resources into mitigation, adaptation and/or productive funds. Resources allocated to mitigation reduce the probability of the loss to the entire group while adaptation investments reduce the magnitude of the loss to the investing agent and productive investments increases payoffs only for the investing agent. We explore subject's response to three treatment conditions; high damage, low damage and heterogeneous damage. Results show that subjects view mitigation and adaptation funds as substitutes in that they contribute higher levels to the adaptation fund if low levels of contributions to the mitigation fund exist, but free-ride on others by contributing to the productive fund if contributions to the mitigation fund are high enough. In particular, we find the highest level of contributions to the socially efficient mitigation fund when all subjects in a group face a high damage and the lowest level when all subjects face a low damage. When high-damage subjects are mixed with low-damage subjects, their contribution levels to the mitigation fund decline, but are still greater than those of their low-damage group members.
Keywords: H41; H87; C92; 330; Collective Action; Climate Change; Economic Experiments